Associated bacterial communities, confrontation studies, and comparative genomics reveal important interactions between Morchella with Pseudomonas spp. - Cailleau, Guillaume; Hanson, Buck T.; Cravero, Melissa; Zhioua, Sami; Hilpish, Patrick; Ruiz, Celia; Robinson, Aaron J.; Kelliher, Julia M.; Morales, Demosthenes; Gallegos-Graves, La Verne; Bonito, Gregory; Chain, Patrick S.G.; et al. (Frontiers in Fungal Biology, 2023)
Members of the fungal genus Morchella are widely known for their important ecological roles and significant economic value. In this study, we used amplicon and genome sequencing to characterize bacterial communities associated with sexual fruiting bodies from wild specimens, as well as vegetative mycelium and sclerotia obtained from Morchella isolates grown in vitro. These investigations included diverse representatives from both Elata and Esculenta Morchella clades. Unique bacterial community compositions were observed across the various structures examined, both within and across individual Morchella isolates or specimens. However, specific bacterial taxa were frequently detected in association with certain structures, providing support for an associated core bacterial community. Bacteria from the genus Pseudomonas and Ralstonia constituted the core bacterial associates of Morchella mycelia and sclerotia, while other genera (e.g., Pedobacter spp., Deviosa spp., and Bradyrhizobium spp.) constituted the core bacterial community of fruiting bodies. Furthermore, the importance of Pseudomonas as a key member of the bacteriome was supported by the isolation of several Pseudomonas strains from mycelia during in vitro cultivation. Four of the six mycelial-derived Pseudomonas isolates shared 16S rDNA sequence identity with amplicon sequences recovered directly from the examined fungal structures. Distinct interaction phenotypes (antagonistic or neutral) were observed in confrontation assays between these bacteria and various Morchella isolates. Genome sequences obtained from these Pseudomonas isolates revealed intriguing differences in gene content and annotated functions, specifically with respect to toxin-antitoxin systems, cell adhesion, chitinases, and insecticidal toxins. These genetic differences correlated with the interaction phenotypes. This study provides evidence that Pseudomonas spp. are frequently associated with Morchella and these associations may greatly impact fungal physiology.